A transversalidade como estratégia de qualificação do trabalho acadêmico: observando o dispositivo Temas em Debate do Programa de Pós-Graduação em Psicologia Social da UFRGS / Transversality as a valuation strategy for academic work: the dispositif of the Topics under Debate Symposium of the Graduate Program in Social Psychology of UFRGS under observation. - Passos, Eduardo (Revista Polis e Psique, 2017)
Conferência